The operational window of carbon nanotube electrical wires treated with strong acids and oxidants - Lepak-Kuc, Sandra; Boncel, S.; Szybowicz, Mirosław; Nowicka, A. B.; Jozwik, I.; Orlinski, K.; Gizewski, Tomasz; Koziol, Krzysztof K.; Jakubowska, M.; Lekawa-Raus, A. (Nature Publishing Group, 2018)
Conventional metal wires suffer from a significant degradation or complete failure in their electrical performance, when subjected to harsh oxidizing environments, however wires constructed from Carbon Nanotubes (CNTs) have been found to actually improve in their electrical performance when subjected to these environments. These opposing reactions may provide new and interesting applications for CNT wires. Yet, before attempting to move to any real-world harsh environment applications, for the CNT wires, it is essential that this area of their operation be thoroughly examined. To investigate this, CNT wires were treated with multiple combinations of the strongest acids and halogens. The wires were then subjected to conductivity measurements, current carrying capacity tests, as well as Raman, microscopy and thermogravimetric analysis to enable the identification of both the limits of oxidative conductivity boosting and the onset of physical damage to the wires. These experiments have led to two main conclusions. Firstly, that CNT wires may operate effectively in harsh oxidizing environments where metal wires would easily fail and secondly, that the highest conductivity increase of the CNT wires can be achieved through a process of annealing, acetone and HCl purification followed by either H2O2 and HClO4 or Br2 treatment.